Effect of Soil and Foliar Application of Plant Nutrients on Purple Blotch and Tip-Burn of Garlic - Faruk Md. Iqbal (Journal of Agronomy Research, 2022)
An experiment was conducted in the field of Plant Pathology Division, BARI, Joydebpur to evaluate the efficacy of available plant nutrient for the development of purple blotch disease and tip-burn of onion. Eight different treatments viz. Potassium (MP fertilizer), Phosphorus (TSP fertilizer), Boron (Boron fertilizer), Zinc (ZnSO4 fertilizer), Calcium (CaSO4 fertilizer), Copper (CuSO4), Silicon (silica gel) and Manganese (MnSO4 fertilizer) were tested against purple blotch disease and tip-burn of garlic. The present study revealed that soil and foliar application of plant nutrients viz. Potassium, Phosphorus, Boron, Zinc, Calcium, Copper, Silicon and Manganese gave appreciable reduction of purple blotch disease and tip-burn incidence and increased plant growth parameters such as shoot and root growth as well as yield of garlic. Among the nutrients Potassium, Phosphorus, Silicon, Zinc and Calcium were performed better for reducing purple blotch disease severity, tip-burn disease incidence and increasing plant growth as well as yield of garlic. Application of Boron and Manganese also performed better than control. So, soil and foliar application plant nutrients Potassium, Phosphorus, Silicon, Zinc, Boron and Manganese may be recommended for tip-burn and purple blotch disease management and for garlic production in Bangladesh.
Keywords: Garlic